The Impact of Cloud-Based Accounting Systems on SME Financial Performance in the Digital Era - Inayah , Ariyanti; Susliyanti , Eni Dwi (Atestasi : Jurnal Ilmiah Akuntansi, 2025)
This study investigates the impact of cloud-based accounting systems (CBAS) on the financial performance of Small and Medium Enterprises (SMEs) in the digital era. As technological innovation increasingly reshapes business operations, SMEs are turning to cloud accounting platforms to enhance their efficiency, transparency, and decision-making processes. This research applies a quantitative approach using a structured questionnaire distributed to 130 SME respondents across various sectors, including services, retail, and manufacturing. The results indicate a significant positive relationship between the use of CBAS and key financial performance indicators, namely profitability, liquidity, and cost efficiency. Regression analysis confirms that cloud adoption contributes to improved financial control and performance, particularly when supported by a high level of digital competency within the organization. Furthermore, the study finds that digital readiness significantly moderates the relationship between CBAS usage and financial performance outcomes. The findings support theoretical models such as the Technology–Organization–Environment (TOE) framework and the Resource-Based View (RBV), emphasizing the role of digital tools as strategic assets. Normatively, this study aligns with global policy directions advocating digital transformation among SMEs as a pathway to enhanced transparency, competitiveness, and inclusion in the formal economy.